1971
DOI: 10.1007/bf01965372
|View full text |Cite
|
Sign up to set email alerts
|

The actions of the chalones

Abstract: In all the ten tissues so far examined it has been found that mitotic activity is controlled by a negative feedback mechanism in which a ehalone molecule acts as the messenger. A ehalone is synthesised within the same tissue on which it specifically acts to inhibit mitosis, it is not speciesspecific, and it has a prolein nature. The characteristics of a chalone mechanism and of its manner of action in a normal tissue are discussed. From studies of a wide range oftumours, both experimental and clinical, it now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In 1962, Bullough and Lawrence first proposed that “diffusible substances,” or chalones, regulate the mass of the specific tissue from which they were derived [ 1 , 40 ]. Shortly after its discovery as a protein synthesized and secreted by skeletal muscle, Lee and McPherron highlighted the potential for myostatin to be a muscle chalone [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1962, Bullough and Lawrence first proposed that “diffusible substances,” or chalones, regulate the mass of the specific tissue from which they were derived [ 1 , 40 ]. Shortly after its discovery as a protein synthesized and secreted by skeletal muscle, Lee and McPherron highlighted the potential for myostatin to be a muscle chalone [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few examples are: lymphokines (for review see [1][2][3]), suppressive factor from T suppressor cells, thymic hormones and other thymic factors [4], and lymphocyte chalones, i.e. factors involved in the control of cell proliferation and differentiation [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with crude water-soluble extracts of proliferating tissues have shown that these extracts may inhibit the mitotic activity of the tissues from which the extracts have been recovered (Bullough, 1971 ;Elgjo, 1972;Iversen, 1973). Bullough (1962) proposed the name 'chalone' to such an extract.…”
mentioning
confidence: 99%